Faktor-Faktor yang Mempengaruhi Kinerja Karyawan: Model Pengujian dengan Variabel Mediasi - Kusjainah Kusjainah; Inon Listyorini (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
Abstract This study discusses faktors influencing employees performance. The independent variabels Motivation and Leadership Styles, while the independence variabel is employees performance.The job satisfaction variabels considered as a variabel mediating the realtion between dependent and independent variabel. Motivation is predicted influencing employees performance directly or indirectly through the variabel job satisfaction. Motivation and leadership style predicted to have a direct effect and an indirect effect through job satisfaction on employee performance. The research subject is the employees who work in profit-oriented organizations around Yogyakarta. Research data are collected through distributing questionnaires toresearch subject. Mediating regression analysis is applied with stepwise regression methods. The result show that motivation and leadership style influence significantly the employee performance. Job Satisfaction Variabels not proved to mediate the relationship Motivation and Leadership Style to Performance. Thus, motivation dan leadership style directly influence the employees performance.